A PRISMA review of expectancy-value theory in music contexts. (May 2022) - Sin, Hui Xing; Tan, Leonard; McPherson, Gary E
In this article, we systematically reviewed the research literature dealing with expectancy-value motivation theory within music contexts. Employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, a total of 1, 120 records were retrieved and examined, with 110 eventually included in the analyses. Frequencies/percentages were generated for research output in 5-year time periods, type of publication, sampling locations, and methodologies. Summaries of all 110 records were provided; content analyses on topics covered were also conducted. Findings indicated a clear increase in research interest over the past 15 years with quantitative methodologies being twice as prevalent as qualitative approaches. While the vast majority (97.7%) of quantitative research employed self-report questionnaires, the most common form of qualitative data collection was interviews (59.1%). Salient topics covered included students' expectancy-value beliefs across music and other school subjects, continued music participation, intentions to pursue a career in music, and parental influences.